Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-21981-z
|View full text |Cite
|
Sign up to set email alerts
|

Leidenfrost droplet trampolining

Abstract: A liquid droplet dispensed over a sufficiently hot surface does not make contact but instead hovers on a cushion of its own self-generated vapor. Since its discovery in 1756, this so-called Leidenfrost effect has been intensively studied. Here we report a remarkable self-propulsion mechanism of Leidenfrost droplets against gravity, that we term Leidenfrost droplet trampolining. Leidenfrost droplets gently deposited on fully rigid surfaces experience self-induced spontaneous oscillations and start to gradually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(56 citation statements)
references
References 32 publications
2
44
0
2
Order By: Relevance
“…Zhong et al [72] reviewed how surface topography and wettability affected the Leidenfrost effect, with a view to droplet geometry and dynamics. Recently, Graeber et al [73] observed an even more complex motion of royalsocietypublishing.org/journal/rsif J. R. Soc. Interface 18: 20210162 7 droplets on an overheated surface and referred to this as Leidenfrost droplet trampolining.…”
Section: Underwater Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhong et al [72] reviewed how surface topography and wettability affected the Leidenfrost effect, with a view to droplet geometry and dynamics. Recently, Graeber et al [73] observed an even more complex motion of royalsocietypublishing.org/journal/rsif J. R. Soc. Interface 18: 20210162 7 droplets on an overheated surface and referred to this as Leidenfrost droplet trampolining.…”
Section: Underwater Environmentmentioning
confidence: 99%
“…For example, the WCA can be reduced by applying an electric field between a conducting droplet and a counter electrode underneath the droplet, which is an electrowetting course without changing the surface structure [28,79]. Previous studies indicated that by changing the applied voltage during electrowetting, the heat-resisting materials can control droplet geometry and dynamic [72,73] royalsocietypublishing.org/journal/rsif J. R. Soc. Interface 18: 20210162…”
Section: Atmospheric Environmentmentioning
confidence: 99%
“…Various impact behaviorse.g., spreading, retraction, rebounding, and splashing-and the resulting crater morphology as well as, liquid marbles have been investigated in detail [8][9][10] . The behaviors of droplets upon impact have been studied comprehensively by experimental [11,12] , theoretical [13,14] , and numerical methods [15] .…”
Section: Introductionmentioning
confidence: 99%
“…There are some relevant works in the field. For example, the study on droplet running uphill from Whitesides et al [30], the recent work on jumping or trampolining drops on surface nanostructures [31,32] and on bouncing drops driven by Marangoni stress [33]. Our previous work [15] focused on transporting a droplet on a wettability-confined gradient surface with the primary objective of finding the optimum wettability confinement.…”
Section: Introductionmentioning
confidence: 99%